Some Ethnophytomedical Aspects and Conservation Strategy of Several Medicinal Plants in Java, Indonesia - HARINI M. SANGAT; INGE LARASHATI (Society for Indonesian Biodiversity, 2002)
The importance of medicinal plants for the preparation of “jamu